Institutional determinants of e-HRM diffusion success. Issue 4 (27th May 2014) - Burbach, Ralf; Royle, Tony
Abstract : Purpose: – Drawing on institutional theory and existing international business practice transfer and e-HRM models this paper develops an e-HRM diffusion model to ascertain the institutional factors that determine the successful diffusion of e-HRM practices in multinational corporations (MNC). The paper aims to discuss these issues. Design/methodology/approach: – The research is based on the analysis of 25 semi-structured interviews with 15 key stakeholders in the German and Irish subsidiaries of a single US-based MNC as well as two interviews with a senior manager in one of its main competitors. Findings: – The findings suggest that the successful transfer of e-HRM is mediated by an interchange of various institutional-level factors (external, relational, organizational and individual) within the corporation and its subsidiaries. Successful implementation of e-HRM is synonymous with the successful integration and institutionalization of e-HRM practices in the subsidiaries. Research limitations/implications: – As this analysis is founded upon a single case study, it is difficult to make assumptions concerning the broad population of all MNC and their subsidiaries. Further research may be required to test the model and the findings presented in this paper. Practical implications: – The findings and the model presented in this paper demonstrate the impact of the institutional context and of key success factors of technology implementation on e-HRM diffusion success. These findings may be of particular relevance to organizations and practitioners who are embarking on an e-HRM installation in an international context. Originality/value: – This paper enriches the e-HRM and international management debate by identifying the key institutional factors impacting the diffusion of e-HRM practices in the subsidiaries of an MNC. In addition, the model put forward in the paper shows how these factors interact and how successful e-HRM diffusion can be characterized.